Advances in laccase-triggered anabolism for biotechnology applications. (3rd October 2021) - Sun, Kai; Li, Shunyao; Si, Youbin; Huang, Qingguo
Abstract: This is the first comprehensive overview of laccase-triggered anabolism from fundamental theory to biotechnology applications. Laccase is a typical biological oxidordeuctase that induces the one-electronic transfer of diverse substrates for engendering four phenoxy radicals with concomitant reduction of O2 into 2H2 O. In vivo, laccase can participate in anabolic processes to create multifarious functional biopolymers such as fungal pigments, plant lignins, and insect cuticles, using mono/polyphenols and their derivatives as enzymatic substrates, and is thus conducive to biological tissue morphogenesis and global carbon storage. Exhilaratingly, fungal laccase has high redox potential ( E ° = 500–800 mV) and thermodynamic efficiency, making it a remarkable candidate for utilization as a versatile catalyst in the green and circular economy. This review elaborates the anabolic mechanisms of laccase in initiating the polymerization of natural phenolic compounds and their derivatives in vivo via radical-based self/cross-coupling. Information is also presented on laccase immobilization engineering that expands the practical application ranges of laccase in biotechnology by improving the enzymatic catalytic activity, stability, and reuse rate. Particularly, advances in biotechnology applications in vitro through fungal laccase-triggered macromolecular biosynthesis may provide a key research direction beneficial to the rational design of green chemistry.